Oxidation of 3-aminobenzanthrone, a human metabolite of carcinogenic environmental pollutant 3-nitrobenzanthrone, by cytochromes P450 - similarity between human and rat enzymes - Mizerovská, Jana; Dračínská, Helena; Arlt, Volker M; Schmeiser, Heinz H; Frei, Eva; Stiborová, Marie (Neuro-endocrinology letters, 2009)
OBJECTIVES: 3-Aminobenzanthrone (3-ABA) is the main human metabolite of carcinogenic environmental pollutant 3-nitrobenzanthrone (3-NBA). Understanding which cytochrome P450 (CYP) enzymes are involved in metabolism of this toxicant is important in the assessment of individual susceptibility. Characterization of 3-ABA metabolites formed by rat hepatic microsomes containing cytochromes P450 (CYPs) and identification of the major rat and human CYPs participating in this process are aims of this study. METHODS: HPLC with UV detection was employed for the separation and characterization of 3-ABA metabolites. Inducers and inhibitors of CYPs and rat and human recombinant CYPs were used to characterize the enzymes participating in 3-ABA oxidation. RESULTS: Selective CYP inhibitors and hepatic microsomes of rats pre-treated with specific CYP inducers were used to characterize rat liver CYPs metabolizing 3-ABA (measured as consumption of 3-ABA). Kinetics of these reactions catalyzed by rat hepatic microsomes was also evaluated. Based on these studies, we attribute most of 3-ABA metabolism in rat liver to CYP1A and 3A. Among recombinant rat and human CYP enzymes tested in this study, rat CYP3A2 and human CYP3A4/5, followed by CYP1A1 of both organisms were the most effective enzymes converting 3-ABA. Rat hepatic CYP enzymes oxidize 3-ABA up to three metabolites. Two of them were identified to be the products formed by oxidation of 3-ABA on its amino group back to the parent compound from which 3-ABA is generated in organisms, 3-NBA. Namely, N-hydroxylation metabolite, N-hydroxy-3-ABA and 3-NBA were identified to be these 3-ABA oxidation products. These metabolites are formed by CYPs of a 1A subfamily. Another 3-ABA metabolite, whose structure remains to be characterized, is generated not only by CYP1A but also by other CYP enzymes, predominantly by CYPs of a 3A subfamily. CONCLUSION: The results found in this study, the first report on the metabolism of 3-ABA by human and rat CYPs, clearly demonstrate that CYPs of 3A and 1A subfamilies are the major enzymes metabolizing 3-ABA.
Keywords: benz(a)anthraceny; Animals; Rats; Kinetics; potkani Wistar; Rats, Wistar; Inhibitory Concentration 50; druhová specificita; vysokoúčinná kapalinová chromatografie; lidé; rekombinantní proteiny; Recombinant Proteins; inhibiční koncentrace 50; Species Specificity; Ultraviolet Rays; jaterní mikrozomy; inhibitory cytochromu P450; oxidace-redukce; Chromatography, High Pressure Liquid; Male; Oxidation-Reduction; systém (enzymů) cytochromů P-450; Microsomes, Liver; krysa rodu Rattus; Benz(a)Anthracenes; zvířata; mužské pohlaví; Cytochrome P-450 Enzyme Inhibitors; kinetika; Cytochrome P-450 Enzyme System; ultrafialové záření; Humans